[PP.07.19] ASSOCIATION OF MAXIMUM SPEED OF BLOOD PRESSURE RISE DURING 24-H ABPM WITH SUBCLINICAL RENAL DAMAGE IN ESSENTIAL HYPERTENSION. (September 2017) - Mule, G.; Gervasi, F.; Vario, M.G.; Cusumano, C.; Salemi, R.; Guarino, L.; Guarneri, M.; Vaccaro, F.; Viola, T.; Cottone, S.
Abstract : Objective: Experimental studies documented that the mechanical injury of intravascular pressure on the vessel wall, which results in vascular remodelling and atherosclerosis, may be more closely associated to oscillatory than to steady laminar shear stress This suggests that the hypertensive patient's prognosis may depend not only on average BP level but also on the degree and rate of BP variation. Little is known about the relationships between early renal abnormalities and the rate of BP changes assessed by intermittent 24-h ambulatory BP monitoring (ABPM). Our study was aimed to analyse the relationships between subclinical renal damage (SRD), defined as the presence of microalbuminuria or an estimated glomerular filtration rate (eGFR) between 30–60 ml/min/1.73 m 2 and the maximum speed of BP rise (Max Slope BP) during a 24-h BP recording Design and method: The study population consisted of 389 untreated essential hypertensives (mean age: 49 ± 13 years; males 58%), which underwent 24-h ABPM, 24-h albumin excretion rate (AER) measurement and GFR estimation, using the CKD-EPI equation. The Max Slope BP was calculated as the first derivative of the curve obtained by fitting partial Fourier series to raw BP data recorded by discontinuous 24-h ABPM. Results: The Max Slope of systolic BP (SBP) was higher in subjects with SRD (n = 117) than in those without SRD (n = 272) (figure) Figure. No caption available. and showed significant correlations with AER (r = 0.215; p < 0.001) and with eGFR (r = - 0.153; p = 0.002). Only the former of these correlations remained significant (β = 0.18; p = 0.001), after adjustment for age, gender, 24 h average SBP and other potential confounders in multiple linear regression analyses. Moreover, multiple logistic regression analysis showed that the probability of having SRD was independently associated with Max Slope SBP (OR: 1.54; p = 0.001). Conclusions: Our results seem to suggest that in essential hypertension, the speed of BP fluctuations are associated with SRD and in particular with microalbuminuria. It is likely that these associations may contribute to explain the increased cardiovascular risk conferred by SRD